From fundamental study to practical application of kerosene in compression ignition engines: An experimental and modeling review. (February 2020) - Lin Tay, Kun; Yu, Wenbin; Zhao, Feiyang; Yang, Wenming
The use of kerosene in direct injection compression ignition engines is fundamentally due to the introduction of the Single Fuel Concept. As conventional direct injection compression ignition diesel engines are made specifically to use diesel fuel, the usage of kerosene will affect engine emissions and performance due to differences between the fuel properties of kerosene and diesel. As a result, in order for kerosene to be properly and efficiently used in diesel engines, it is needful for the scientific community to know the properties of kerosene, its autoignition and combustion characteristics, as well as its emissions formation behavior under diesel engine operating conditions. Moreover, it is desirable to know the progress made in the development of suitable kerosene surrogates for engine applications as it is a crucial step toward the development of reliable chemical reaction mechanisms for numerical simulations. Therefore, in this work, a comprehensive review is carried out systematically to better understand the characteristics and behavior of kerosene under direct injection compression ignition engine relevant conditions. In this review work, the fuel properties of kerosene are summarized and discussed. In addition, fundamental autoignition studies of kerosene in shock tube, rapid compression machine, fuel ignition tester, ignition quality tester, constant volume combustion chamber, and engine are compiled and evaluated. Furthermore, experimental studies of kerosene spray and combustion in constant volume combustion chambers are examined. Also, the experimental investigations of kerosene combustion and emissions in direct injection compression ignition engines are discussed. Moreover, the development of kerosene surrogates, their chemical reaction mechanisms, and the modeling of kerosene combustion in direct injection compression ignition engines are summarized and talked about. Finally, recommendations are also given to help researchers focus on the areas which are still severely lacking.